The Phenomenon of Islamic Literature as a Tool For Educating Muslim in Indonesia (A Reflection To Increase the Verbal Intelligence) - Yulianti, Eka; Hamzah, Syukri (Jurnal Pendidikan Tambusai, 2021)
Generally, there?s a lot of tool and way to educate people, one of them is islamic literature. Islam and literature are two captivating element to collaborate. Literature has a beautiful language which could entertain the reader. Then Islam enter to the literature as a science. When Islam combined with the literature, so it such as something alive. Islam and literature like one soul and body, breathe, and doing a movement. In Indonesia, islamic literature has been exist since 14th century coincide with the spread of Islam in Archipelago. However on that era, the educational processes through islamic literature still on the reading activity. With thus, the Indonesian muslim's society who will be educated through islamic literature are only worked at the circle of muslims who like the activity of reading. Nowadays, islamic literature in Indonesia more develop than before. How popular is it, the islamic literature such as islamic novels who written by the Indonesian muslim's writer now has been made into the movie. One of the Indonesian famous muslim?s writer, he is Habiburrahman El-Shirazy, most of his novels has been made into movies, like Ayat- Ayat Cinta (Verses of Love) which is published on 2004, then it has been made into a movie on 2008. His other novels like Ketika Cinta Bertasbih (When Love Glorifies God) which is published on 2007 also has been made into a movie on 2009, and Dalam Mihrab Cinta (In Mihrab?s Love) which is published on 2010 also has been made into a movie in the same year, 2010. Beside Habiburrahman El-Shirazy, there are Asma Nadia who her novels are not only made into movies, but it also has been made into drama in television, Hanum Salsabila Rais who all of her novels based on true story and its background on the abroad also has been made into the movies. Then, Ahmad Fuady, Helvy Tiana Rosa, ect, who most of their novels also has been made into the movies. This phenomenon is what makes islamic literature as a tool for educating muslim in Indonesia. If in the classic era, islamic literature only educates the muslim who like reading activity, however in the contemporer era like nowadays, islamic literature has success entering the film?s world, so the range of educational processes through islamic literature become wider. The aim of this research are to describe about how Islam educates the muslim's reader through the art of literature. Beside that, the aim is also to support the Indonesian muslim?s writer to keep productive in creating the art of literature which has an islamic nuance in order to create the religious and broadminded?s society. Study of this research is through investigation's activity from research?s result which is concerning to the topic. The conclussion of this research is showing that islamic literature is not only about the divinity, however it is also cover about the humanity. Islamic literature guides the human to hold on to the humanity values, good manners values, honesty, simplicity, and patience to face the life. These value are crucial for human in this contemporer era like nowadays, where the values has been scarce. The educational processes through islamic literature by inserting the text of Al-Qur?an and Hadith could cover all circles, not only Indonesian muslims who like reading islamic literature that will be educated, but also the society who prefers the activity of watching will be educated too, because the popularity of islamic literature in Indonesia nowadays has penetrating the film?s world.